(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Denture-related infections are a growing concern in both clinical and community health settings, especially among the elderly. Poor hygiene practices, combined with ill-fitting or long-term prostheses, have contributed to the rise of suppurative (pus-forming) infections such as denture stomatitis, angular cheilitis, and even systemic mycoses. This paper explores the microbial risks associated with denture use, emphasizing how inadequate hygiene can lead to localized epidemics, biofilm formation, and serious systemic complications. It also discusses the dentist’s role in early detection, patient education, and public health prevention strategies.